Bacteria of the genus Rickettsia in ticks (Acari: Ixodidae) collected from birds in Costa Rica - Ogrzewalska, Maria; Literák, Ivan; Capek, Miroslav; Sychra, Oldřich; Calderón, Víctor Álvarez; Rodríguez, Bernardo Calvo; Prudencio, Carlos; Martins, Thiago F; Labruna, Marcelo B (Ticks and tick-borne diseases, 2015)
The aim of this study was to document the presence of Rickettsia spp. in ticks parasitizing wild birds in Costa Rica. Birds were trapped at seven locations in Costa Rica during 2004, 2009, and 2010; then visually examined for the presence of ticks. Ticks were identified, and part of them was tested individually for the presence of Rickettsia spp. by polymerase chain reaction (PCR) using primers targeting fragments of the rickettsial genes gltA and ompA. PCR products were DNA-sequenced and analyzed in BLAST to determine similarities with previously reported rickettsial agents. A total of 1878 birds were examined, from which 163 birds (9%) were infested with 388 ticks of the genera Amblyomma and Ixodes. The following Amblyomma (in decreasing order of abundance) were found in immature stages (larvae and nymphs): Amblyomma longirostre, Amblyomma calcaratum, Amblyomma coelebs, Amblyomma sabanerae, Amblyomma varium, Amblyomma maculatum, and Amblyomma ovale. Ixodes ticks were represented by Ixodes minor and two unclassified species, designated here as Ixodes sp. genotype I, and Ixodes sp. genotype II. Twelve of 24 tested A. longirostre ticks were found to be infected with 'Candidatus Rickettsia amblyommii', and 2 of 4 A. sabanerae were found to be infected with Rickettsia bellii. Eight of 10 larval Ixodes minor were infected with an endosymbiont (a novel Rickettsia sp. agent) genetically related to the Ixodes scapularis endosymbiont. No rickettsial DNA was found in A. calcaratum, A. coelebs, A. maculatum, A. ovale, A. varium, Ixodes sp. I, and Ixodes sp. II. We report the occurrence of I. minor in Costa Rica for the first time and a number of new bird host-tick associations. Moreover, 'Candidatus R. amblyommii' and R. bellii were found in A. longirostre and A. sabanerae, respectively, in Costa Rica for the first time.
Keywords: Ticks; Animals, Wild; Ixodes; Tick Infestations; Bird Diseases; Birds; infestace klíšťaty; divoká zvířata; Rickettsia; nemoci ptáků; zvířata; Ixodidae; larva; Larva; Costa Rica; ptáci; Amblyomma; Kostarika; Animals